Pengaruh Struktur, Budaya, dan Kompetensi terhadap Kinerja Organisasi Pemerintah dengan Kepemimpinan Transformasional sebagai Variabel Moderasi - Oktaviani, Leny; Istianda, Meita; Kuswandi, Aos (Jurnal Pemerintahan dan Politik, 2025)
This study aims to examine the influence of bureaucratic structure, organizational culture, and employee competence on organizational performance, with transformational leadership as a moderating variable at the Deputy for Regional Research and Innovation, National Research and Innovation Agency. A quantitative approach was employed, and data were analyzed using the SEM-PLS (Structural Equation Modeling - Partial Least Square) method, a multivariate data analysis technique combining factor analysis and regression, acilitated by the SmartPLS 4 Application. The population consisted of 546 regional agencies responsible for research, development, assessment, and application, as well as invention and innovation in local governments, with a total of 248 regional agencies respondents. The results that bureaucratic structure and employee competence significantly affect on organizational performance, while organizational culture does not. Transformational leadership positively moderates the relationship between bureaucratic structure and organizational performance but negatively moderates the relationship between employee competence and organizational performance. Conversaly, transformational leadership does not moderate the relationship between organizational culture and organizational performance. The results provide recommendations for improving organizational performance by improving adaptive bureaucratic structures and increasing employee competence on an ongoing basis, as well as strengthening organizational culture as a factor supporting organizational performance. Furthermore, adjustments to the transformational leadership approach can strengthen structure and competence.